PENINGKATAN KEPUASAN PELANGGAN INTERNAL DAN EKSTERNAL MELALUI DESAIN ULANG PROSES LAYANAN DAN KPI YANG JELAS - Riduan Siagian; Parlaban Karo-Karo; Nur Marliana Harum HRP (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This PkM program aims to improve the satisfaction of internal customers (between units/staff) and external customers (community/students/parents/partners) through redesigning service processes based on user needs and implementing clear and measurable KPIs. Common problems include convoluted service flows, unclear service time standards, inconsistent information, ineffective complaint channels, and unmonitored service performance. Interventions are carried out through mapping as-is processes, measuring satisfaction baselines, identifying root causes, designing to-be processes and service standards (SOP & SLA), preparing KPIs and dashboards, training service officers, as well as pilot testing and continuous improvement. Outputs include end-to-end service SOPs, service catalogs, SLAs, KPIs, monitoring dashboards, and before-after impact reports